ANALYZING AUTHOR’S ATTITUDE OF THE THESIS ABSTRACT WRITTEN BY AN UNDERGRADUATE STUDENT OF ENGLISH DEPARTMENT: A PATH FOR CRITICAL REVIEW - Misdi Misdi (Universitas Putera Batam, 2015)
An abstract is the most important part of the thesis. Good abstract shows the content of the writing. It is a verbatim form of text which is concise and informative so that the readers easily deduce the content of the paper. However, abstract sometimes shows a lack of minimum requirement. Hence, it indicates the authors’ attitude as well as their critical writing. Using data taken from the undergraduate students of English department of private university in Indramayu, West Java, author’s attitude and his writing skill were criticized. The results of the analysis suggest that the author’s attitude and skill were challenged in terms of appraisal and modality. Grammar problem was also discussed. As the implication, this study suggests the framework how to check and criticize students’ writing before their texts are published.